Reliability of the triangle completion test in the real-world and in virtual reality - McLaren, Ruth; Chaudhary, Shikha; Rashid, Usman; Ravindran, Shobika; Taylor, Denise (Frontiers in Human Neuroscience, 2022)
Background The triangle completion test has been used to assess egocentric wayfinding for decades, yet there is little information on its reliability. We developed a virtual reality (VR) based test and investigated whether either test of spatial navigation was reliable. Objective To examine test-retest reliability of the real-world and VR triangle completion tests. A secondary objective was to examine the usability of the VR based test. Materials and methods Thirty healthy adults aged 18–45 years were recruited to this block randomized study. Participants completed two sessions of triangle completion tests in the real-world and VR on the same day with a break between sessions. Results In both test versions distance from the endpoint and angle of deviation showed poor test-retest reliability (r < 0.5). Distance traveled had moderate reliability in both the real-world and VR tests (r = 0.55 95% CI [0.23, 0.76]; r = 0.66 95% CI [0.4, 0.83, respectively]). The VR triangle test showed poor correlation with the real-world test. Conclusion The triangle completion test has poor test-retest reliability and demonstrates poor concurrent validity between the real-world and VR. Nevertheless, it was feasible to translate a real-world test of spatial navigation into VR. VR provides opportunities for development of clinically relevant spatial navigation tests in the future.